COMBINING ABILITY FOR INHERITANCE OF ECONOMIC TRAITS IN OPIUM POPPY (Papaver somniferum L.) (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Opium poppy (Papaver somniferum L.) is an important medicinal plant produces more than 80 alkaloids obtained from the capsules and straw of the plant. The estimate of combining ability gives an indication of the genetic behaviour of the parental material. It is therefore, desirable to select the parents for hybridization on the basis of their per se performance and combining ability effects. The F1, F2 and their reciprocals of an eight parent diallel cross in opium poppy were studied for combining ability of seven economic traits. The mean sum of squares due to GCA, SCA and reciprocals were significant for all the traits. The magnitude of GCA variances were invariably higher than those of SCA and thus indicating the preponderance of non-additive genetic variances, which was further affirmed by the measure of average degree of dominance i.e. ?(?2s/? 2g).  Among the parents VN35I for plant height, Sanchita and VG26 for capsules per plant, VN23, VN35I and Vivek for capsule index, VG26 and Sanchita for seed and straw yield per plant, and VN35I and VG20 for morphine content were found good general combiners. Earliness being a desired trait, parent VG20 having significant negative GCA estimates coupled with per se performance can be considered as good general combiner for early flowering. Inclusion of good general combiners in a multiple crossing program or an inter-mating population involving all possible crosses among them subjected to bi-parental mating may be expected to offer maximum promise in breeding for economic traits.DOI: http://dx.doi.org/10.3329/bjpbg.v24i2.17000